Effect of Milling and Annealing on Carbon-Silver System - Martynková, Gražyna Simha; Becerik, Fatih; Plachá, Daniela; Pang, Jinbo; Akbulut, Hatem; Bachmatiuk, Alicja; Rummeli, Mark H (Journal of nanoscience and nanotechnology, 2019)
Mechanical treatment of graphite silver mixture followed by heat treatment showed morphology and structure changes of both components. Silver is being distributed over graphite flakes randomly with higher concentration on the edges and nanometric size, which was observed using scanning and transmission electron microscopy. The annealing temperature 1300 °C is higher than melting temperature of silver (961.8 °C) and base on phase diagram C-Ag (C. L. Chen, et al., Appl. Phys. Lett. 96, 253104 (2010).) silver is being transferred from liquid phase to solid phase at rapid cooling, which is giving various crystallinity.